Sleeve Gastrectomy Reduces Glycemia but Does Not Affect Cognitive Impairment in Lean 5xFAD Mice - Samuel, Itia; Ben-Haroush Schyr, Rachel; Arad, Yhara; Attali, Tamar; Azulai, Shira; Bergel, Michael; Halfon, Aviv; Hefetz, Liron; Hirsch, Tamir; Israeli, Hadar; Lax, Neta; Nitzan, Keren; et al. (Frontiers in Neuroscience, 2022)
Obesity and hyperglycemia are risk factors for the development of cognitive decline, and Alzheimer’s Disease (AD). Bariatric surgery is an effective treatment for obesity that is reported to have also weight loss independent effects on metabolic diseases such as type 2 diabetes. In this study we tested whether sleeve gastrectomy (SG), a common bariatric surgery, can affect the cognitive impairment in lean, normoglycemic female 5xFAD mice, a genetic model for AD. 5xFAD mice and wild type (WT) littermates underwent SG or sham surgery at the age of five months, close to clinical disease onset, and were tested for metabolic, behavioral and histological phenotypes 90 days later. SG led to a reduction in blood glucose levels and total plasma cholesterol levels in 5xFAD mice without inducing weight loss. However, surgery had no effect on the outcomes of long-term spatial memory tests in these mice. Histological studies on the presence of -Amyloid plaques corroborated the behavioral studies in showing no effect of surgery on the molecular phenotype of 5xFAD mice. In conclusion, SG leads to an improved metabolic profile in lean female 5xFAD mice without inducing weight loss, but has no effect on the brain pathology or behavioral phenotype. Our results suggest that the positive effects of bariatric surgery on cognitive decline in patients are likely attributed to weight loss.